P405 Long-term safety of 3 years of ozanimod in moderately to severely active ulcerative colitis: an interim analysis of the True North open-label extension. (30th January 2023) - Panaccione, R; Danese, S; Wolf, D C; Canavan, J B; Jain, A; Wu, H; Petersen, A; Charles, L; Afzali, A; Abreu, M T
Abstract: Background: The phase 3, randomised True North (TN) study demonstrated the efficacy and safety of ozanimod for up to 52 weeks in patients (pts) with moderately to severely active ulcerative colitis (UC). The ongoing TN open-label extension (OLE) aims to assess the long-term efficacy and safety of ozanimod in UC. This analysis evaluated the cumulative long-term safety of ozanimod in these studies, which included pts with up to ~3 years of treatment exposure. Methods: In TN, pts were randomised to once-daily ozanimod 0.92 mg or placebo, or to open-label ozanimod for a 10-week induction period. Ozanimod clinical responders were rerandomised at Week 10 to ozanimod or placebo in the maintenance period through Week 52. TN pts were eligible to enrol in the OLE and receive ozanimod if they did not achieve clinical response at the end of induction (Week 10), lost response during maintenance, or completed maintenance at Week 52. This interim analysis of the TN OLE (data cutoff: 10 January 2022) included all pts who entered the OLE from TN (n=823). Safety was monitored from the first dose of ozanimod in TN and throughout the subsequent OLE. Exposure-adjusted incidence rates per 100 patient-years (PY) were calculated. Results: The average age of TN OLE study participants was 41.7 years (±13.6), 41% were female, 62% had left-sided UC disease, and 35% had prior exposure to tumor necrosis factor inhibitors. Total PY exposure to ozanimod was 2219 years (mean [SD] exposure = 2.7 [1.6]). The most frequent treatment-emergent adverse events (TEAEs) reported through OLE Week 94 (up to 146 weeks of continuous treatment) are listed in the Table. Most TEAEs were nonserious; TEAEs leading to discontinuation were uncommon. Bradycardia was reported in 3 pts (0.4%; EAIR 0.1/100 PY; 2 in TN and 1 in OLE; no pts were discontinued from treatment). Macular edema was reported in 2 (0.2%; EAIR 0.1/100 PY) pts. Reductions in ALC were common (470 [57.1%] had ALC < 500 cells/mm 3 ), as previously described, but ALC reductions were not associated with the occurrence of TEAEs. Malignancies were uncommon (n=13 [1.6%]; EAIR 0.6/100 PY), and included 6 basal cell carcinomas and 3 colorectal neoplasms. Two deaths were reported: 1 due to COVID-19 and 1 sudden death. Investigators deemed both to be unrelated to treatment. Ozanimod was not associated with an increased risk of ischemic heart disease or thromboembolic events. Conclusion: Long-term exposure to ozanimod for up to 3 years was well tolerated in pts with moderately to severely active UC. No new safety signals were observed with long-term ozanimod use in UC (2219 PY exposure). Safety findings are consistent with previous reports from the UC and multiple sclerosis development programs (>16, 512 PY exposure).